Performance and Diversity of Gravitational Search Algorithm - Nor Azlina, Ab. Aziz; Marizan, Mubin; Zuwairie, Ibrahim; Sophan Wahyudi, Nawawi (The Institute of Internet, Broadcasting and Communication, 2014)
GSA is a physic inspired optimization algorithm. It is based on how bodies in the universe are attracted to each other by gravitational force between them. The performance of GSA is studied here using benchmark functions. The diversity of the search agents of GSA is also studied. The findings show that research on improvement of GSA algorithm are needed, specifically in improving the search agents’ diversity.